Perfusion parameters and target values during extracorporeal cardiopulmonary resuscitation: a scoping review protocol - Saemann, Lars; Schmucker, Christine; Rösner, Lisa; Beyersdorf, Friedhelm; Benk, Christoph (BMJ open, 2019)
Introduction  Extracorporeal cardiopulmonary resuscitation (eCPR) is increasingly applied in out-ofhospital cardiac arrest (OHCA) and in-hospital cardiac arrest (IHCA) patients. Treatment results are promising, but the efficacy and safety of the procedure are still unclear. Currently, there are no recommended target perfusion parameters during eCPR, the lack of which could result in inadequate (re)perfusion. We aim to perform a scoping review to explore the current literature addressing target perfusion parameters, target values, corresponding survival rates and neurologic outcomes in OHCA and IHCA patients treated with eCPR. Methods and analysis  To identify relevant research, we will conduct searches in the electronic databases MEDLINE, EMBASE, Social Science Citation Index, Social Science Citation Index Expanded and the Cochrane library. We will also check references of relevant articles and perform a cited reference research (forward citation tracking).